The State of Female Youth in Northern Uganda: Findings from the Survey of War Affected Youth - Annan, Jeannie; Blattman, Christopher; Carlson, Khristopher; Mazurana, Dyan (Tufts Archival Research Center, 2005)
Youth have been both the primary victims and the primary actors in the twenty-two year war between the Government of Uganda and the Lord's Resistance Army. It was not clear, however, exactly who is suffering, how much, and in what ways. For instance, researchers knew little about the experience of youth: what is the magnitude, incidence, and nature of the violence, trauma, and suffering of youth in northern Uganda? An understanding of the effects of war on women and girls was particularly lacking, whether they were abducted or affected by the violence in other ways.